Urban space, crisis and coexistence in La villa to César Aira (Revista de Crítica Literaria Latinoamericana, 2014)
La villa by Argentinian writer César Aira recounts the struggles and changes experienced by two different social groups: on the one hand, poor and marginalized people living in shanty towns called villas miseria and, on the other hand, a group of upper middle class people who live in a traditional neighborhood. Our reading focuses on the shared spaces portrayed in the novel. Our aim is to underline the social differences and the criticisms exposed by a divided urban distribution. We will also study the personal relationships described in the story, as well as new ways of living together in the city. Our analysis involves three different perspectives found in this narrative: a realist reading, a fairy tale structure and interpretation, and a recreation of the story done by the media portrayed in the novel.
Keywords: community; recent Argentine literature; urban spaces; Buenos Aires; César Aira